Relationship Between Circulating Netrin-1 Concentration, Impaired Fasting Glucose, and Newly Diagnosed Type 2 Diabetes - Yim, Jisook; Kim, Gyuri; Lee, Byung-Wan; Kang, Eun Seok; Cha, Bong-Soo; Kim, Jeong-Ho; Cho, Jin Won; Lee, Sang-Guk; Lee, Yong-ho (Frontiers in Endocrinology, 2018)
Background: The protein netrin-1 has demonstrated anti-inflammatory, tissue regeneration, and immune modulation properties. Although inflammation is a major contributing factor in the development of insulin resistance and type 2 diabetes, little is known about a possible relationship between serum netrin-1 and type 2 diabetes. Therefore, we investigated the association between circulating levels of netrin-1 and glycometabolic parameters predictive of type 2 diabetes. Methods: Serum samples were collected from 41 normal controls, 85 subjects with impaired fasting glucose (IFG), and 92 subjects with newly diagnosed type 2 diabetes. Clinical and laboratory parameters were assessed and netrin-1 levels were measured by commercial enzyme-linked immunosorbent assay. Spearman correlation analyses and multivariable-adjusted regression analyses were conducted to examine the relationship between serum netrin-1 levels and glycometabolic parameters. Results: Serum netrin-1 levels in subjects with type 2 diabetes or IFG were significantly higher compared to normal controls (441.0 pg/mL, 436.6 pg/mL, and 275.9 pg/mL, respectively; P for trend <0.001). Serum netrin-1 levels were significantly positively correlated with fasting glucose, HbA1c, and insulin resistance index (all Ps<0.01). Serum netrin-1 levels were independently associated with IFG or type 2 diabetes (standardized β=0.405, P <0.001) after adjusting for covariates and potential confounders. In addition, the receiver operating characteristic (ROC) analysis showed that serum netrin-1 levels could identify the presence of IFG and type 2 diabetes with the area under the ROC curve (AUC) of 0.784 (P <0.001). Conclusions: Our results suggest that elevated serum netrin-1 levels are significantly associated with the presence of IFG and type 2 diabetes.